Comparison of vaccine effectiveness against influenza hospitalization of cell-based and egg-based influenza vaccines, 2017–2018. Issue 39 (16th September 2019) - Bruxvoort, Katia J.; Luo, Yi; Ackerson, Bradley; Tanenbaum, Hilary C.; Sy, Lina S.; Gandhi, Ashesh; Tseng, Hung Fu
Abstract: Egg-based influenza vaccines could be less effective than cell-based vaccine due to adaptive mutations acquired for growth. We conducted a test-negative case-control study at Kaiser Permanente Southern California to assess vaccine effectiveness (VE) against hospitalization for laboratory-confirmed influenza during 2017–2018. Among the 1186 cases and 6946 controls, 74% and 59%, respectively, were ages ≥ 65 years. For any influenza, the adjusted relative VE of cell-based vaccine versus egg-based vaccines was 43% (95% CI: −45% to 77%) for patients ages < 65 years and 6% (95% CI: −46% to 39%) for patients ages ≥ 65 years. For influenza A(H3N2), the adjusted relative VE was 61% (95% CI: −63% to 91%) for patients ages < 65 years and −4% (95% CI: −70% to 37%) for patients ages ≥ 65 years. Statistically significant protection against influenza hospitalization of cell-based vaccine compared to egg-based vaccines was not observed, but further studies in additional influenza seasons are warranted.